The ATP-P2X7 Signaling Pathway Participates in the Regulation of Slit1 Expression in Satellite Glial Cells - Zhang, Quanpeng; Zhao, Jiuhong; Shen, Jing; Zhang, Xianfang; Ren, Rui; Ma, Zhijian; He, Yuebin; Kang, Qian; Wang, Yanshan; Dong, Xu; Sun, Jin; Liu, Zhuozhou; et al. (Frontiers in Cellular Neuroscience, 2019)
Slit1 is one of the known signalling factors of the slit family and can promote neurite growth by binding to its receptor, Robo2. Upregulation of Slit1 expression in dorsal root ganglia (DRG) after peripheral nerve injury plays an important role in nerve regeneration. Each sensory neuronal soma in the DRG is encapsulated by several surrounding satellite glial cells (SGCs) to form a neural structural unit. However, the temporal and spatial patterns of Slit1 upregulation in SGCs in DRG and its molecular mechanisms are not well understood. This study examined the spatial and temporal patterns of Slit1 expression in DRG after sciatic nerve crush by immunohistochemistry and western blotting. The effect of neuronal damage signalling on the expression of Slit1 in SGCs was studied in vivo by fluorescent gold retrograde tracing and double immunofluorescence staining. The relationship between the expression of Slit1 in SGCs and neuronal somas was also observed by culturing DRG cells and double immunofluorescence labelling. The molecular mechanism of Slit1 was further explored by immunohistochemistry and western blotting after intraperitoneal injection of Bright Blue G (BBG, P2X7R inhibitor). The results showed that after peripheral nerve injury, the expression of slit1 in the neurons and SGCs of DRG increased. The expression of Slit1 was presented with a time lag in SGCs than in neurons. The expression of Slit1 in SGCs was induced by contact with surrounding neuronal somas. Through injured cell localization, it was found that the expression of Slit1 was stronger in SGCs surrounding injured neurons than in SGCs surrounding non-injured neurons. The expression of vesicular nucleotide transporter (VNUT) in DRG neurons was increased by injury signalling. After the inhibition of P2X7R, the expression of Slit1 in SGCs was downregulated, and the expression of VNUT in DRG neurons was upregulated. These results indicate that the ATP-P2X7R pathway is involved in signal transduction from peripheral nerve injury to SGCs, leading to the upregulation of slit1 expression.